(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
Analysis of the Marz physical-geography role during the formation of thermal regime, estimate the regularities of spatio-temporal distribution of the air temperature is the goal of the work. Close correlation links between absolute height of area and air and soil temperatures, as well as, those between air and soil temperatures have been got. So, in perennial data of Marz observes a tendency of increasing of air and soil temperature values.